Implementasi Program untuk Peningkatan Cakupan Imunisasi Human Papillomavirus (HPV) - Khosyi, Vania Intana; Suryawati, Chriswardani; Arso, Septo Pawelas (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Human Papillomavirus immunization is one of the programs for the prevention of cervical cancer. The program targets 90% of school-age girls, 70% of cervical cancer patients aged 35-45 years, and 90% of women undergoing cancer treatment. School-based immunization is included in the national immunization program carried out in various countries. This immunization program is very effective but there are still obstacles in its implementation. The purpose of this study was to determine the supporting and inhibiting factors for the implementation of the Human Papillomavirus immunization program in preventing cervical cancer. This study was a literature review. Article searches were conducted on the Scopus database at levels Q1 to Q4, resulting in 148 articles to be selected according to the established criteria. The selection process obtained 9 articles regarding the implementation of the Human Papillomavirus immunization program. The results of the review showed that there were supporting and inhibiting factors. Supporting factors included accessibility and public funding, the role of health workers or parties involved, and strategies in education. While inhibiting factors included lack of knowledge, parental permission, reporting mechanisms, socioeconomic problems, and lack of stakeholder involvement. It could be concluded that various supporting factors and inhibiting factors in program implementation can affect the success of the Human Papillomavirus immunization program in the future.Keywords: immunization; human papillomavirus; program implementation ABSTRAK Imunisasi Human Papillomavirus merupakan salah satu program untuk pencegahan penyakit kanker serviks uteri. Sasaran program adalah 90% pada anak perempuan masih sekolah, 70% pad penderita kanker serviks uteri berusia 35-45 tahun, dan 90% pada pengobatan perempuan dengan kanker. Imunisasi berbasis sekolah masuk dalam program imunisasi nasional yang dilakukan di berbagai negara. Program imunisasi ini sangat efektif tetapi masih ada kendala dalam pelaksanaannya. Tujuan dari studi ini adalah mengetahui faktor pendukung dan penghambat pelaksanaan program imunisasi Human Papillomavirus dalam pencegahan penyakit kanker serviks uteri. Studi ini merupakan tinjauan literatur. Penelusuran artikel dilakukan pada database Scopus pada level Q1 sampai Q4, sehingga didapatkan 148 artikel untuk diseleksi sesuai dengan kriteria yang telah ditetapkan. Proses seleksi mendapatkan 9 artikel mengenai implementasi program imunisasi Human Papillomavirus. Hasil tinjauan menunjukkan bahwa terdapat faktor pendukung maupun penghambat. Faktor pendukung mencakup aksesabilitas dan pendanaan publik, peran tenaga kesehatan atau pihak yang terlibat, dan strategi dalam edukasi. Sedangkan faktor penghambat antara lain kurangnya pengetahuan, perijinan orang tua,  mekanisme pelaporan, masalah sosioekonomi, dan kurangnya keterlibatan pemangku kepentingan. Dapat disimpulkan bahwa berbagai faktor pendukung dan faktor penghambat pelaksanaan program dapat mempengaruhi keberasilan program imunisasi Human Papillomavirus di masa mendatang.Kata kunci: imunisasi; human papillomavirus; implementasi program